METODOLOGÍA PARA EL DESARROLLO DE CURSOS VIRTUALES DE APOYO AL APRENDIZAJE COMBINADO EN EL BACHILLERATO UNIFICADO DEL ECUADOR - WALFREDO GONZÁLEZ HERNÁNDEZ; RICARDO PATRICIO MEDINA CHICAIZA (Revista Ingeniería, Matemáticas y Ciencias de la Información)
The article presents the problem of designing virtual courses for combined learning in the unified baccalaureate ofEcuador. Subsequently, an analysis of the considerations about this problem is made from defining the blearning as anorganizational form, the design of virtual courses and how they are designed. Subsequently, the actions of the proposedmethodology are broken down.